The effects of social misdirection on magic tricks: How deceived and undeceived groups differ - Tachibana, Ryo (Iperception, 2014)
Characteristics of perception and cognition in our daily lives can be elucidated through studying misdirection, a technique used by magicians to manipulate attention. Recent findings on the effects of social misdirection induced by joint attention have been disputed, and differences between deceived (failed to detect the magic trick) and undeceived (detected the magic trick) groups remain unclear. To examine how social misdirection affects deceived and undeceived groups, we showed participants movie clips of the “cups & balls,” a classic magic trick, and measured participants' eye positions (i.e. where participants looked while viewing the clips) using an eye tracker. We found that the undeceived group looked less at the magician's face than the deceived group. These results indicate that deceived individuals have difficulty trying not to allocate attention to the face. We conclude that social misdirection captures attention, influencing the emergence of deception.